2007
DOI: 10.1002/hup.873
|View full text |Cite
|
Sign up to set email alerts
|

The neuropsychology of ecstasy (MDMA) use: a quantitative review

Abstract: A growing number of empirical studies have found varying neuropsychological impairments associated with use of 3,4-methylenedioxymethamphetamine (MDMA) use. We set out to determine to what extent neuropsychological abilities are impaired in MDMA users. To do so, meta-analytical methods were used to determine the magnitude of neuropsychological impairment in MDMA users across pre-specified cognitive domains. We found that cognitive impairment secondary to recreational drug use may result in what might be descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 64 publications
6
65
0
3
Order By: Relevance
“…The most consistent behavioral differences that have been reported in abstinent MDMA users have been subtle cognitive deficits, [23][24][25][26] behavioral impulsivity, 30,31 altered sleep architecture, 30 and altered neuroendocrine function. 32,33 The present study provides evidence that MDMA exposure increases the risk for obstructive sleep apnea, with rates of sleep apnea and hypopnea being directly related to prior MDMA exposure.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The most consistent behavioral differences that have been reported in abstinent MDMA users have been subtle cognitive deficits, [23][24][25][26] behavioral impulsivity, 30,31 altered sleep architecture, 30 and altered neuroendocrine function. 32,33 The present study provides evidence that MDMA exposure increases the risk for obstructive sleep apnea, with rates of sleep apnea and hypopnea being directly related to prior MDMA exposure.…”
Section: Resultsmentioning
confidence: 92%
“…[22][23][24][25][26] This possibility is raised by the fact that chronic sleep disruption is known to have a deleterious effect on daytime cognitive functioning. 34 Thus, arousals during sleep secondary to nocturnal hypopneas and apneas could play a role in subtle changes in Blue diamonds represent apnea hypopnea index values for subjects in methylenedioxymethamphetamine (MDMA) and control groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, both cross-sectional and, more rarely, longitudinal studies have suggested MDMA associated deficits on a variety of assessments of learning and memory performance [13]. Reported MDMA-associated impairments involve multiple cognitive domains, including executive function and planning, working memory, and retrospective as well as prospective memory [11] [31]- [37]. Unfortunately, when considered from a methodological viewpoint, definitive conclusions derived from this body of research are problematic [30].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the euphoric acute effects, however, recreational use of ecstasy is associated with a range of deleterious effects on neuropsychological and physical wellbeing. The effects on cognition are well documented and detailed in several comprehensive reviews (cf Murphy et al, 2009;Solowij & Battisti, 2008;Zakzanis et al, 2007); however, in brief, although deficits are observed across a range of cognitive domains, the most consistent effects are observed in learning and memory tasks that involve high levels of executive functioning (e.g., Reay et al 2006). Chronic use is also associated with increases in psychological morbidity.…”
Section: Introductionmentioning
confidence: 99%